The Grammaticalization to Conjunction of Verb “thaem” in Thai - Thawarorit, Sriangkarn; Udomphan, Cherdchai (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This research article investigates the grammaticalization of the conjunction of the verb "thaem" in historical Thai. The data were collected from the Thai National Corpus and prose works from the Sukhothai Period to the present (B.E. 2560). The information gathered was put into three periods: 1) the Sukhothai Period, 2) the Ayutthaya Period up to the reign of King Rama III, and 3) the reign of King Rama IV up to the present. The research findings were presented using an analytical description. The results showed that the word "thaem" contained two functions. The first function is that of the verb, which can be divided into three types: intransitive verbs that mean "adding to," transitive verbs that mean "adding to," and transitive verbs that mean "adding something to,’ and a ditransitive verb meaning ‘adding something for.’ The second function is the conjunction for ‘adding more content." The verb "theam" first appeared during King Rama VI's reign and is now used as a conjunction. The context conducive to the grammaticalization of the verb into the conjunction was the transitive verb with the meaning of 'adding something to'. The grammaticalization was quite complete and progressed gradually. Notably, "thaem" was used as conjunction 84.29% of the time, while it was used as a verb 15.71% of the time. "Thaem" has been through the following two syntactic mechanisms: reanalysis and analogy. Moreover, it has been through semantic changes in metaphor and metonymy. Such grammaticalization resulted in 5 linguistic changes: 1) generalization, 2) recategorization, 3) specialization, 4) divergence, and 5) renewal. The grammaticalization was also found in gradual changes in a linear fashion. The results demonstrated the grammatical trend in Thai and the functional and semantic change of the verb into the conjunction, which could be examined through grammaticalization.